Zrównoważony rozwój w tradycji prawnej Chińskiej Republiki Ludowej - Bazylińska-Nagler, Justyna (Wydawnictwo Uniwersytetu Wrocławskiego, 2021)
An old Chinese saying says: “Nature and man joined into one whole” (Tian Ren He Yi). One could think that Chinese political thought, extensively bound to religion, philosophy, and tradition, laid perfect foundations for the implementation of public international law sustainable development principles. However, Chinese totalitarianism irreversibly changed the perception of the relation between humans and nature that used to be deeply rooted in traditional culture. The purpose of this work was to analyze the evolution of Chinese attitude towards sustainable development that serves environmental protection. The key issue concerning the Chinese willingness to fulfill their international obligations concerning sustainable development had to be addressed. Equally important was the question about the integration principle in Chinese law which would imply balancing environmental needs with economic development in all state politics as it does in the EU law under article 11 of the Treaty on the Functioning of the European Union. The research shows that Chinese environmental law has been notably shaped by public international law in correlation to its standards and has developed significantly for the last 35 years. A good example may be the amendment of 2014 of Chinese Environmental Law that implemented expressis verbis sustainable development as a priority before economic development. However, it seems to be a landmark change, opening new research fields considering its future execution. Considering the above, this work concludes with some moderate but ironic optimism linked to the current plan of the People’s Republic of China to build „ecological civilization.”
Keywords: tradycja prawna; Chińska Republika Ludowa; konfucjanizm; totalitaryzm; autorytaryzm; despotyzm; zasada ogólna prawa międzynarodowego; zrównoważony rozwój